O068 EVAR Gore salvage fabric technique (ARAFAT) to salvage evar fabric fatigue and graft failure. (22nd July 2022) - Sultan, S; Acharya, Y; Hynes, N
Abstract: Introduction: EVAR GORE SalvAge Fabric Technique (ARAFAT) is an innovative management protocol to seal material graft failure due to type IIIb endoleak (EL) in patients who are mainly at high risk for open conversion. We aim to discuss ARAFAT, an innovative management protocol to seal material graft failure due to type IIIb endoleak (EL). Methods: We employed ARAFAT in patients following type IIIb EL to salvage previous EVAR with a polyester-based stent graft. The ARAFAT principle relies on the use of polytetrafluoroethylene (PTFE) and the realignment of the polyester stent graft for sealing the microleaks and aortic sac hygroma, resulted due to polyester filtration. First, an oversized EXCLUDER® aortic cuff (GORE®, Flagstaff, Arizona, USA) is deployed into the previously implanted polyester-based stent graft. This is followed by simultaneous deployment of an EXCLUDER® iliac extension, as necessary, in double barrel configuration from the main cuff. A minimum of 2 cm of a distal seal zone is provided to promote stability. Results: ARAFAT was employed in 18 patients (mean age 80 ± 6.86 years; 77% male). The average size of the aortic sac that underwent re-intervention was 6.68 ± 2.13 cm. All the patients had primary technical success. There was no peri-operative mortality. The average follow-up was 35.6 ± 6.24 months. Conclusion: We successfully employed the ARAFAT technique as a fully functioning protocol to overcome apparent challenges in managing material fatigue graft failure EL in high-risk patients. Take-home message: EVAR GORE Salvage Fabric Technique (ARAFAT) technique could be successfully employed as a fully functioning protocol to overcome apparent challenges in managing material fatigue graft failure EL in high-risk patients.